Construction of a novel disulfidptosis and cuproptosis-related lncRNA signature for predicting the clinical outcome and immune response in stomach adenocarcinoma - Caihao Qu; Xin Yan; Futian Tang; Yumin Li (Discover Oncology)
Abstract Background Disulfidptosis, a newly discovered form of cell death resulting from disulfide stress, remains unclear in its role in stomach adenocarcinoma (STAD). This study aimed to establish a novel disulfidptosis and cuproptosis-related lncRNAs (DCRLs) signature for STAD. Methods We sourced RNA-seq data for STAD from the The Cancer Genome Atlas (TCGA) repository. STAD samples underwent nonnegative matrix factorization (NMF) clustering to identify distinct molecular subgroups, followed by Lasso-Cox regression to construct a prognostic model for DCRLs. Subsequently, the model’s clinical predictive capacity was evaluated using a nomogram. The expression of risk lncRNAs was validated via quantitative reverse transcription polymerase chain reaction (qRT-PCR). Results The samples were classified into three molecular subtypes based on DCRLs, with the C1 subtype demonstrating the worst prognosis. We identified four independent prognostic lncRNAs (AC016394.2, NUTM2A-AS1, OIP5-AS1, and LIMS1-AS1) and constructed a prognostic risk model. Survival analysis revealed that high-risk patients had a poorer prognosis. The model’s risk score was strongly correlated with the tumor mutational burden (TMB), microsatellite instability (MSI), immune subtypes, and tumor-infiltrating immune cells (TIICs) in the tumor microenvironment (TME). Analysis utilizing the Tumor Immune Dysfunction and Exclusion (TIDE) revealed a higher risk of tumor immune evasion among high-risk patients. Moreover, the expression levels of four risk lncRNAs were higher in the majority of gastric cancer cell lines compared to normal cell lines. Conclusion Our study establishes a risk model that effectively predicts clinical outcomes and immune response in STAD.